Characterization and Antimicrobial Studies of Iturin-Like and Bogorol-Like Lipopeptides From Brevibacillus spp. Strains GI9 and SKDU10 - Singh, Shelley Sardul; Sharma, Deepika; Baindara, Piyush; Choksket, Stanzin; Harshvardhan,; Mandal, Santi M.; Grover, Vishakha; Korpole, Suresh (Frontiers in Microbiology, 2021)
Members of the genus Brevibacillus have been demonstrated to produce a variety of bioactive compounds including polyketides, lipopeptides and bacteriocins. Lipopeptides are non-ribosomally synthesized surface active compounds with antimicrobial, antitumor and immune-stimulatory activities. They usually exhibit strong antifungal activities and are considered as promising compounds in controlling fungal diseases. In this study, we have characterized two lipopeptides from by Brevibacillus sp. strains GI9 and SKDU10. The corresponding lipopeptides were purified by reverse phase high-performance liquid chromatography. Mass analysis and characterization by MALDI-TOF-MS analysis revealed production of an iturin-like lipopeptide by strain GI9 and bogorol-like lipopeptide by strain SKDU10. Both lipopeptides exhibited broad spectrum antibacterial activity and inhibited growth of various fungi. They showed MIC values between 90-300 μg/ml against indicator strains of bacteria and drug resistant Candida indicator strains. The lipopeptides did not show phytotoxic effect in seed germination experiments but caused hemolysis. Further, both lipopeptides inhibited the growth of fungi on fruits and vegetables in in-vitro experiments, thereby exhibited potential use in biotechnological industry as effective biocontrol agents.